Chemical Analysis of Environmental Conditions of Seaweed Culture In Pulo Raya, Kabupaten Aceh Jaya, Aceh Province - Muhammad Ridwan Harahap (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
Research has been carried out on the analysis of the environmental conditions of seaweed cultivation in the Pulo Raya area of Aceh Jaya Regency, Aceh Province. Aceh Province is the westernmost province of the Indonesian archipelago. Geographically, Aceh is a peninsula area of the island of Sumatra which is directly bordered by the Indian Ocean so that Aceh has several small islands. With this condition, it has the potential to be used as a place for seaweed cultivation. An analysis of environmental conditions is needed to produce good quality seaweed. Examination parameters include pH, temperature, heavy metal content, COD and salinity. Sample examination is carried out based on Standar Nasional Indonesia (SNI) No. 7578.1: 2010 and Decree of the Minister of Environment (KemenLH) No. 51: 2004. The results obtained showed a pH level of 6.22; temperature of ± 28 oC; levels of lead metal ions (Pb (II)) 0.001 ppm and copper (Cu (II) metal ions of 0.002 ppm; The COD level is 137 ppm and the salinity level is 28.75 ppm. With the results of the chemical analysis obtained, the Pulo Raya area is feasible to become a seaweed cultivation area.